Brain Drain or Brain Gain? Graduate Migration in Old Industrial Regions - Analysis of the Central Lower Rhine Area, Germany - Angelika Jaeger; Fabian Kreutzer (European Regional Science Association (ERSA), 2012)
The influence of tertiary education on the economic development of a region is a topic of special interest and prevalent object of studies and discussions of regional economists. Universities are frequently referred to as 'creative hubs'. Researching universities are generally expected to be one of the key institutions around which growth occurs, determining the direction of regional economic development. Especially the large number of highly-educated graduates is of eminent importance in terms of regional competitive advantages. If graduates remain in the university's region, they form and enrich a highly educated labour force and support knowledge and innovation transfer from the university to the regional economy, networks, and enterprises. Human capital has traditionally been observed to be one of the most important resources of regions and one of the key factors explaining economic growth. In any economic region, gaining insights into the phenomenon of regional graduate migration and the determinants and reasons behind it is highly relevant for regional economic analysis and a prerequisite for policy recommendations. This holds especially true for old industrial regions with structural problems and low economic growth potential - as the Central Lower Rhine Area in North-Rhine-Westphalia, Germany, subject of this study. These regions depend on knowledge and innovation transfer from universities to overcome problems associated with industrial structural changes and market turmoil, and to face problematic trends as the forthcoming demographic development. The research aim of this article is to analyse the migration of graduates in the Central Lower Rhine Area by assessing the regional 'brain flow' originating from the Niederrhine University of Applied Sciences (NR UAS), its only institution of higher education. More detailed objectives concern the assessment of the distribution of migration patterns, migration motives, graduate characteristics influencing the migration decision, and the comparison of actual migration patterns with migration preferences. Our results show that for the Central Lower Rhine Area, the associated regional brain drain resulting from graduate emigration cannot be compensated by extra-regional brain gain. A likely reason for this is a deficit of absorption capacity exhibited by the regional economy: A large proportion of graduates migrate due to difficulties finding an adequate job, or respectively, are attracted by economically better performing regions. Furthermore, econometric analysis identifies certain graduate characteristics influencing the migration decision. Remarkably, the migration decision is only marginally influenced by soft location factors like quality of living, regional image, or recreational amenities. Summarized, the research findings describe, interpret, and explain the regional graduate migration patterns and motives and indicate interesting implications.
Keywords: I23; O15; 330; University Graduates; Migration Patterns; Determinants and Motives; Alumni Network